THEORY OF CONTRACTS IN THE LIGHT OF NEW INSTITUTIONAL ECONOMICS. THE SPECIFICITY OF AGRICULTURAL CONTRACTS - Lemanowicz, Marzena (Acta Scientiarum Polonorum. Oeconomia, 2018)
The article reviews Polish and foreign economic literature regarding new institutional economics (NIE) and various research approaches used in the framework of NIE. Particular attention was paid to the economic theory of contracts and the transaction costs, as the limitation of transaction costs is indeed the main stimulus for contract signing. Special attention was given to agricultural contracts and their specificity. The article discusses different theories applied in the analysis of contracts, characterizes contracts according to different criteria, and draws attention to the importance of transaction costs in the theory of contracts. In addition, factors which contribute to these costs have been identified, indicating the necessity of adapting the principles of transaction cost economics to the needs of the agricultural sector.